Control of a Security Door Through the Internet of Things - Toapanta, Jonathan (2022)
Home security has increased in recent years with the help of technology. Even more, the appearance of the internet of things (IoT) allows it to control and monitor devices from anywhere in the world. This work develops a proposal that alerts the user about the status of a door through a mobile application using low-cost devices. For the electronic design, a magnetic contact sensor has been used that detects if the door is open. An electric lock is also used to control the door with the mobile application from anywhere in the user. The electronic system is based on an ESP32 board that has WiFi communication, this board sends the door status data to the mobile application. The electric lock can be activated in three ways: manually from the door, automatically according to a programmed routine, and remotely using the mobile app. The platform used for the IoT is Firebase, which allows the exchange of information between the local site and the remote site. The tests carried out around the prototype have responded correctly, the installed sensor continuously reports on the status of the door, and the control is executed according to the orders sent through the cloud. In addition, an acceptance test is used that guarantees the correct operation of the proposal.